Managing and measuring for value: the case of call centre performance - Marr, Bernard; Neely, Andrew (Cranfield School of Management and Fujitsu, 2004)
As an integral part of most organisations today call centres play a key role in the service delivery chain. Value creation is in the eye of the beholder, if organisations fail to deliver value to their customers, there will inevitably be a loss for stakeholders over the longer term. Presently in many industries, call centres are the primary source of contact for customers. This important role implies that the performance management of call centres is of critical importance to organisations, especially the delivery of customer satisfaction. In this research the ways organisations measure and manage customer satisfaction in call centres is explored. Clear evidence that current measures of performance in call centres are often counter-productive to achieving customer satisfaction is revealed. Many call centres seem to have fallen into the trap of believing that operational measures such as call duration are indicators of customer satisfaction. Evidence indicates that they are not; they are only measures of efficiency, which in turn is seen as determinant of financial performance. Most call centres seem to miss the important link between employee satisfaction, service quality, customer satisfaction, and profitability. In 12 case studies of world-leading call centres, the research identifies various managerial implications to avoid the "efficiency trap" in measuring and managing call centre performance. The managerial implications of this research are as follows: l Call centre performance is increasingly important for delivering customer service. Call centre performance should not be measured in isolation from the performance of the whole organisation. In most cases they are not detached operations with a solitary goal of driving down costs. Call centres are an integral part of an organisations value chain delivering its services and products. Therefore, the performance measures of call centres need to reflect the strategic direction of the entire organisation. l A more balanced approach to measuring performance based on strategic objectives is valuable, especially if visual representations of service delivery and value creation are used. This enables easy communication of overall performance and puts efficiency targets in perspective. Best practice seems to be to track the following areas of performance as well as their interactions: employee satisfaction, service quality, customer satisfaction, and satisfaction of other stakeholders (e.g. financial performance) with particular emphasis on the intangible performance drivers. l Customer dialogue is important and call centres are in fact listening to and speaking with customers all the time. Measuring customer satisfaction should start with understanding customers. Communication is often very task orientated, whereas call centres need to recognise the importance of listening to the customers in order to: - understand their needs and requirements from their perspective - detect failures, bottle necks, or improvement potential - deliver service that satisfies the customer. l It is critical to understand and classify the nature of demand. Often calls are unwanted or even unwittingly generated by other parts of the organisation. By analysing and classifying demand, it becomes more manageable and more predictable. Unwanted calls could then be reduced or even eliminated. Overall, a strategy-driven and integrated approach towards performance measurement in call centres will, therefore, improve operational efficiency and contribute to continuous innovation of the organisation as a whole.
Research Report for publication by Cranfield School of Management and Fujitsu